Putting Eastern Europe Back Into Western Civilization: Or, Why Is The Russian Stuff Always At The End? - Cox, John (Teaching History: A Journal of Methods, 2002)
This essay offers a brief description of efforts by a specialist to rework courses for a general curriculum. Needless to say, this adaptation is a common concern for faculty at colleges and small universities. Where there is a strong core curriculum, professors are often called upon to teach surveys or other general courses that include but move well outside their specialties. My own graduate work was in East European history; my foreign research languages are Serbian, German, Slovene, and Hungarian; my visceral frames of reference for historical questions are quintessentially East European concepts such as nationalism, irredenta, great power hegemonism, lagging economic modernization, linguistic diversity, and cultural fault lines; my dissertation was a biography of a revisionist Yugoslav communist. But much of my time in our required freshmen classes is spent teaching a lot of different material, from Hatshepsut to Hiroshima. My colleagues have similar experiences. How do we adapt, and what constructive perspectives can a specialist bring to a general course?